Penggunaan Model Pembelajaran Snowball Throwing untuk Meningkatkan Hasil Belajar Peserta Didik Tema Benda di Sekitarku Kelas III SD Negeri 02/X Parit Culum II Semester Ganjil Tahun Ajaran 2022/2023 - Juli Martati (Journal on Education, 2022)
The purpose of this study was to obtain information and discuss the use of the snowball throwing learning model to improve student learning outcomes on the theme of objects around me in class III SD Negeri 02/X Parit Culum II odd semester of the 2022/2023 academic year. This research is a classroom action research which consists of two cycles. This research was conducted at SDN 02/X Parit Culum for the academic year 2022/2023 odd semester with 18 class III students as research subjects. Data collection techniques using tests, observations, field notes and documentation. Data were analyzed using percentages and data reduction. From the results of the research and discussion it can be concluded that through the snowball throwing type cooperative learning model it can improve student learning outcomes on the theme of objects around me in class III SD Negeri 02/X Parit Culum II even semester of the 2022/2023 school year by giving rewards